IMPLEMENTASI PROGRAM KERJA KEPALA SEKOLAH TERHADAP KINERJA GURU DI SMP-IT NURUL ILMI - Khairunniswah Khairunniswah; Yusuf Hadi Jaya; Inom Nasution (Universitas Islam Negeri Sumatera Utara Medan, 2021)
This researcher aims to determine: (1) the principal's work program planning on teacher performance at SMP-IT Nurul Ilmi, (2) the principal's efforts to implement the principal's work program on teacher performance at SMP-IT Nurul Ilmi, (3) implementation barriers Principal's work program on teacher performance at SMP-IT Nurul Ilmi.The method used in this study is qualitative using data collection techniques in the form of observation, interviews, and documentation with an emphasis on information data sources, namely: school principals, vice principals, administration, and English teachers to strengthen the validity of the data obtained. From the results of this study using three findings, namely: (1) the principal's work program planning on teacher performance at SMP-IT Nurul Ilmi has been carried out well, carried out in the form of meetings and deliberation with the teachers, (2) the principal's efforts to implement The principal's work program on teacher performance at SMP-IT Nurul Ilmi is carried out by giving assignments to teachers according to the field of ability and work according to expertise, (3) obstacles to implementing the principal's work program on teacher performance at SMP-IT Nurul Ilmi are carried out by teachers while working to find out how far the improvement in teacher performance has been.Keywords: Work Program, Teacher Performance